In vitro Antimicrobial Studies of the Essential Oil of Vitis adnata - Srivastava, Mahesh (Asian Journal of Chemistry, 2010)
Investigations of the antimicrobial therapeutic behaviour of phytochemicals have been the interest of scientists in recent years and scores of phytochemicals have shown promising results.